Combining genetic and epigenetic parameters of the serotonin transporter gene in obsessive-compulsive disorder. (January 2018) - Grünblatt, Edna; Marinova, Zoya; Roth, Alexander; Gardini, Elena; Ball, Juliane; Geissler, Julia; Wojdacz, Tomasz K.; Romanos, Marcel; Walitza, Susanne
Abstract: While genetic variants have been reported to be associated with obsessive-compulsive disorder (OCD), the small effect sizes suggest that epigenetic mechanisms such as DNA methylation may also be relevant. The serotonin transporter ( SLC6A4 ) gene has been extensively investigated in relation to OCD, since serotonin reuptake inhibitors are the pharmacological treatment of choice for the disorder. The current study set three questions: Firstly, whether the high expressing loci of the SLC6A4 polymorphisms, 5-HTTLPR + rs25531, rs25532 and rs16965628 are associated with family-based (n = 164 trios) and case-control OCD (n = 186, 152, respectively). This was also examined by a meta-analysis. Secondly, whether DNA methylation and RNA levels of the SLC6A4 differ in saliva and blood of a subset of samples from pediatric and adult OCD patients and matched controls. And lastly, whether morning awakening cortisol levels correlate with the above. A meta-analysis confirmed the association of the LA -allele with OCD (OR = 1.21, p = 0.00018), maintaining significance in the early-onset OCD subgroup (OR = 1.21, p = 0.022). There was no association between rs25532 or rs16965628 and OCD. Our preliminary data showed that SLC6A4 DNA methylation levels in an amplicon located at the beginning of the first intron were significantly higher in the saliva of pediatric OCD patients compared to controls and adult patients with OCD, but no alterations in RNA levels or in polymorphism interactions were observed. Morning awakening salivary cortisol levels positively correlated with methylation levels, and negatively correlated with RNA levels. This study further supports the involvement of the SLC6A4 gene in OCD through both genetic and epigenetic mechanisms. This finding needs to be explored further in an independent large sample.